MODELING OF LOCAL SCOUR IN ABUTMENT BRIDGE USING SSIIM-2 - Rohmah, Nailul
A bridge that crosses over a river affects the flow characteristics, which is an increase in the current that passes under the bridge and the turbulent flow that is formed produces local scours that endanger the bridge structure. The purpose of this scour modeling research on the abutment of the Rahabangga bridge on the Konaweha River is to analyze the mechanism of water flow and velocity vector with the conditions before the abutment and the condition after the abutment, as well as to analyze the mechanism of scour in the river with conditions before the abutment and the condition after the abutment. The method used in the scour pattern simulation on the Rahabangga bridge abutment at Konaweha River is to use numerical modeling with the SSIIM 2 (Sediment Simulation in Intakes with Multiblock Option) with return period of discharge 50 th 1950.863 m3/s The running result using SSIIM-2 on the water flow mechanism before and after the abutment is a change in the velocity vector that forms a vortex around the bridge abutment, there is also an increase in the value of shear stress at the base to the end of the abutment, then for the running results of the sediment there is also a change in the bed level of the river around the bridge abutments. Local scour solution in this study was done by spreading riprap rock, where the grain diameter was changed to 0.3 m as an assumption in the computation to change the rock around the abutment into riprap rock, from the computation results obtained change of scour depth around the bridge again the depth occurred at 2,745 m to 1,408 m From the results of analysis using modeling with SSIIM 2 produces visualizations in the form of changes in water flow, shear stress and bed level changes in river contours, from the visualization in SSIIM-2 it can be concluded that the mechanism of water flow and bed level changes in river contours can be described in detail using the SSIIM 2-program, also riprap implementation can be reduction depth of scour around the bridge abutment.